Multivariate geostatistical methods for analysis of relationships between ecological indicators and environmental factors at multiple spatial scales - Ribeiro, Manuel Castro; Pinho, Pedro; Llop, Esteve; Branquinho, Cristina; Sousa, António Jorge; Pereira, Maria João; Castro, Manuel; Jorge, António; João, Maria (Ecological Indicators, 2013)
As all biodiversity-related variables, ecological indicators are influenced by environmental factors working at different spatial scales. However, assessing the relationship between environmental factors and ecological indicators is limited to a set of spatial scales determined a priori. This a priori assumption can hide important relationships, especially for ecological indicators with a complex spatial structure that can be driven, for example, by the influence of multiple pollutants with different dispersion ranges or by the influence of local and regional factors such as land-cover and climate. To relate ecological indicators and environmental factors without assuming a priori spatial scales of analysis, we used a Linear Model of Coregionalization. This method has been used in literature to analyze the joint distribution of biodiversity variables. Here we show that it can be used to gain insight into spatial patterns of relationships between ecological indicators and underlying environmental factors. We applied this method to a region of south-west Europe, relating data from land-cover, altitude and climate with an ecological indicator, the abundance of fruticose lichen species, known to be very sensitive to multiple environmental factors. Based on variogram analysis we identified distinct spatial scales of relationships between the ecological indicator and environmental factors. For each spatial scale we described relationships using Principal Component Analysis applied to the coregionalization matrices. This way we could assess how strong the relationship between each environmental factor and ecological indicator at each spatial scale was: at medium scales (c. 15 km) open spaces areas (a proxy for particle emissions) were more important; at larger scales (c. 45 km) open spaces, artificial areas (a proxy for gaseous pollutants) and also climate were preponderant. Thus, multivariate geostatistics provided a tool to improve knowledge on relationships between ecological indicators and environmental factors at multiple spatial scales without setting a priori spatial scales of analysis.
Keywords: biomonitoring; linear model of coregionalization; Multivariate geostatistics; spatial analysis

Leaf accumulation of trace elements and polycyclic aromatic hydrocarbons (PAHs) in Quercus ilex L. - De Nicola, F.; Maisto, G.; Prati, M. V.; Alfani, A. (Environmental pollution (Barking, Essex : 1987), 2008)
Quercus ilex L. leaves were collected four times in one year at six urban sites and one remote area in order to determine trace element and PAH accumulation through concomitant analyses of unwashed and water-washed leaves. Both unwashed and washed leaves showed the highest amounts of trace elements and PAHs in the urban area. Unwashed leaves showed greater differences between urban and remote areas and among the urban sites than washed leaves for trace element and PAH concentrations. Water-washing resulted in a significant (P<0.001) decrease in leaf concentrations of Cr, Cu, Fe, Pb, V and Zn. By contrast, Cd and total PAH concentrations showed no differences between unwashed and washed leaves.
The following values have no corresponding Zotero field: accession-num: 17892907
Keywords: Air Pollutants; Air Pollutants: analysis; Aromatic; Aromatic: analysis; Atomic; biomonitoring; cadmium; Cadmium: analysis; chromium; Chromium: analysis; Cities; copper; Copper: analysis; Environmental Monitoring; Environmental Monitoring: methods; Iron; Iron: analysis; Italy; lead; Lead: analysis; PAHs; Plant Leaves; Plant Leaves: chemistry; Polycyclic Hydrocarbons; Quercus; Quercus ilex L.; Spectrophotometry; Trace Elements; Trace Elements: analysis; Unwashed and washed leaves; Vanadium; Vanadium: analysis; Zinc; Zinc: analysis

Leaf accumulation of trace elements and polycyclic aromatic hydrocarbons (PAHs) in Quercus ilex L. - De Nicola, F; Maisto, G; Prati, M V; Alfani, a (Environmental pollution (Barking, Essex : 1987), 2008)
Quercus ilex L. leaves were collected four times in one year at six urban sites and one remote area in order to determine trace element and PAH accumulation through concomitant analyses of unwashed and water-washed leaves. Both unwashed and washed leaves showed the highest amounts of trace elements and PAHs in the urban area. Unwashed leaves showed greater differences between urban and remote areas and among the urban sites than washed leaves for trace element and PAH concentrations. Water-washing resulted in a significant (P<0.001) decrease in leaf concentrations of Cr, Cu, Fe, Pb, V and Zn. By contrast, Cd and total PAH concentrations showed no differences between unwashed and washed leaves.
Keywords: Air Pollutants; Air Pollutants: analysis; Aromatic; Aromatic: analysis; Atomic; biomonitoring; cadmium; Cadmium: analysis; chromium; Chromium: analysis; Cities; copper; Copper: analysis; Environmental Monitoring; Environmental Monitoring: methods; Iron; Iron: analysis; Italy; lead; Lead: analysis; PAHs; Plant Leaves; Plant Leaves: chemistry; Polycyclic Hydrocarbons; Quercus; Quercus ilex L.; Spectrophotometry; Trace Elements; Trace Elements: analysis; Unwashed and washed leaves; Vanadium; Vanadium: analysis; Zinc; Zinc: analysis

Leaves of Quercus ilex L. as biomonitors of PAHs in the air of Naples (Italy) - Alfani, Anna; Maisto, Giulia; Vittoria Prati, Maria; Baldantoni, Daniela (Atmospheric Environment, 2001)
Polycyclic aromatic hydrocarbons (PAHs)were determined by the GC-MS chromatography in the leaves of Quercus ilex L., an evergreen Mediterranean oak, to monitor the degree of pollution in the urban area of Naples compared to remote areas. Leaf samples were collected in July 1998 from four urban parks, six roadsides and two sites in remote areas. The total PAH contents in Q. ilex leaves ranged from 106.6 in a control site to 4607.5 ng/g d.w. along a road with a high tra$c #ow. The mean concentration factors (urban/control)were 3.8 for the parks and 15 for the roads. The contribution of carcinogenic PAHs (benz[a]anthracene, benzo[b]#uoranthene, benzo[k]#uoranthene, benzo[a]pyrene, dibenz[a,h]anthracene, indeno[1,2,3-c,d]pyrene)was higher in urban area and di!ered according to the site, ranging from 6.7% to 21.3%. The total PAH burden in control sites was dominated by the low molecular weight PAHs, whilst along the urban roads #uoranthene, pyrene and benz[a]anthracene among the measured PAHs showed the highest values. PAHs were positively correlated (P(0.01)to trace metals measured in a previous study.
Keywords: biomonitoring; leaves; polycyclic aromatic hydrocarbons; Quercus ilex L; rural and urban areas

Leaves of Quercus ilex L. as biomonitors of PAHs in the air of Naples (Italy) - Alfani, Anna; Maisto, Giulia; Vittoria Prati, Maria; Baldantoni, Daniela (Atmospheric Environment, 2001)
Polycyclic aromatic hydrocarbons (PAHs)were determined by the GC-MS chromatography in the leaves of Quercus ilex L., an evergreen Mediterranean oak, to monitor the degree of pollution in the urban area of Naples compared to remote areas. Leaf samples were collected in July 1998 from four urban parks, six roadsides and two sites in remote areas. The total PAH contents in Q. ilex leaves ranged from 106.6 in a control site to 4607.5 ng/g d.w. along a road with a high tra$c #ow. The mean concentration factors (urban/control)were 3.8 for the parks and 15 for the roads. The contribution of carcinogenic PAHs (benz[a]anthracene, benzo[b]#uoranthene, benzo[k]#uoranthene, benzo[a]pyrene, dibenz[a,h]anthracene, indeno[1,2,3-c,d]pyrene)was higher in urban area and di!ered according to the site, ranging from 6.7% to 21.3%. The total PAH burden in control sites was dominated by the low molecular weight PAHs, whilst along the urban roads #uoranthene, pyrene and benz[a]anthracene among the measured PAHs showed the highest values. PAHs were positively correlated (P(0.01)to trace metals measured in a previous study.
Keywords: biomonitoring; leaves; polycyclic aromatic hydrocarbons; Quercus ilex L; rural and urban areas

Dendroanalysis: a tool for biomonitoring environmental pollution? - Nabais, C; Freitas, H; Hagemeyer, J (The Science of the total environment, 1999)
Trees of temperate regions usually form visible annual growth rings, which can be dated accurately. It is therefore possible to collect wood samples of different age and analyse their heavy metals content in order to get a chronological record of trace elements pollution in the tree's environment. This method of retrospective biomonitoring was called dendroanalysis. A basic assumption of dendroanalysis is the stability of the mineral distribution patterns, i.e. once the elements are stored, no significant mobility should occur. Additionally, neighbouring trees growing in the same environment should show similar radial element patterns. While some studies presented good correlations between radial distributions of heavy metals in tree rings and temporal records of pollution from industry or traffic, others failed in using dendroanalysis as a chronological record of pollution. Probably some elements can move at a certain rate in radial direction through the ray parenchyma cells. In this way the radial element distributions are subsequently changed. Growth rates of tree rings can also influence the concentrations of elements in wood. During periods of slow growth higher concentrations of elements can be found in the wood. Therefore, radial distribution patterns of heavy metals in tree rings should be used with caution as a tool for retrospective biomonitoring of environmental pollution.
Keywords: biomonitoring; Dendroanalysis; Heavy metals

Heavy Metals in Moss and Bark From Urban Area of Florence: A New Cleaness Procedure for Removing Superficial Particulate Matter - Ducceschi, L; Legittimo, P Cellini; Bonzi, L Morassi (Chemistry and Ecology, 1999)
Abstract Hypnum cupressiforme epiphytic moss and tree bark (elm and holm oak) samples have been collected in three sites of the city of Florence in the period 1995?1998. Lead, zinc, copper, and cadmium were determined by differential pulse anodic stripping voltammetry (DPASV) in about 200 samples collected at different heights above ground. A new clean-up procedure by nitrogen jet has been followed and its efficiency has been also verified by electron microscopy (SEM and ESEM techniques). Lead median contents in moss and bark samples fall within the ranges of 0.052?0.86 and 0.20?1.30 ?moles g?1 (dry weight), resulting values for moss and bark are proportional to the vehicular traffic density. the increasing use of lead-free gasoline has not been followed by a decrease of lead moss concentration.
doi: 10.1080/02757549908037642
Keywords: Bark; biomonitoring; environmental scanning electron microscopy (ESEM); Heavy metals; Moss

Heavy Metals in Moss and Bark From Urban Area of Florence: A New Cleaness Procedure for Removing Superficial Particulate Matter - Ducceschi, L.; Legittimo, P. Cellini; Bonzi, L. Morassi (Chemistry and Ecology, 1999)
Abstract Hypnum cupressiforme epiphytic moss and tree bark (elm and holm oak) samples have been collected in three sites of the city of Florence in the period 1995?1998. Lead, zinc, copper, and cadmium were determined by differential pulse anodic stripping voltammetry (DPASV) in about 200 samples collected at different heights above ground. A new clean-up procedure by nitrogen jet has been followed and its efficiency has been also verified by electron microscopy (SEM and ESEM techniques). Lead median contents in moss and bark samples fall within the ranges of 0.052?0.86 and 0.20?1.30 ?moles g?1 (dry weight), resulting values for moss and bark are proportional to the vehicular traffic density. the increasing use of lead-free gasoline has not been followed by a decrease of lead moss concentration.
doi: 10.1080/02757549908037642doi: 10.1080/02757549908037642The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: Bark; biomonitoring; environmental scanning electron microscopy (ESEM); Heavy metals; Moss

Tree bark as a bioindicator of air pollution in Navarra, Spain - Santamaria, J M; Martin, A (Water, Air, & Soil Pollution, 1997)
During a two year research period from 1992 to 1993, samples of different species of trees were taken in 17 forest stands located in Navarra, Spain. From these samples, bark extracts were prepared in which the pH and the conductivity were measured. The health of the sampling trees was also evaluated by determining the degree of defoliation and decoloration of the canopies. The bark tissue analysis revealed the presence of an environmental acidity gradient that decreased from NW to SE. This coincides with the location of important sources of pollution and their course of transport and dispersion. On the other hand, in the samples of Quercus ilex a significant correlation between the pH and the defoliation levels (P<0.01, r = 0.62) was found. This fact reveals the potential usefulness of tree bark as a health bioindicator of trees.
Keywords: air pollution; Bioindicator; biomonitoring; Tree bark

Trace metal biomonitoring in the soil and the leaves of Quercus ilex in the urban area of Naples. - Alfani, a; Bartoli, G.; Rutigliano, F. a; Maisto, G.; De Santo, a V. (Biological trace element research, 1996)
The concentrations of Pb, Cu, Fe, and Mn were analyzed in surface deposit and tissue of Quercus ilex leaves from several sites of the urban area of Naples, exposed to different degrees of air pollution. These included some major roads with heavy traffic loads, squares, and three urban parks. The soil from the trunk base area of Q. ilex trees in the same sites was also analyzed for total and available metal contents. Pb, Cu, and Fe contents in the surface deposit and leaf tissue were significantly higher (p < 0.01) in leaves from roadside sites than in leaves from parks; significant correlations were found between deposit- and tissue-contents of Pb, Cu, and Fe. Mn content in leaves from roadside sites and in leaves from parks were similar and Mn content in the leaf deposit was irrelevant. Significant differences (p < 0.001) in both total and available Pb and Cu soil content were found between sampling sites. Also for available Fe and Mn soil content differences among sites were relevant, although the highest values were measured in soil from urban parks. A positive correlation between leaf and soil metal content was found only for Pb, thus suggesting that trace metal contents of leaves directly depend on atmospheric depositions. Seasonal variations of Pb, Cu, and Fe were pronounced at a polluted site, whereas no relevant seasonal variation was observed at a control site; moreover, metal accumulation was high at the polluted site. Mn content and seasonal dynamics were comparable at control and polluted sites.
The following values have no corresponding Zotero field: accession-num: 8834387
Keywords: Air Pollutants; Air Pollutants: analysis; biomonitoring; copper; Copper: analysis; Environmental Monitoring; Holly Oak; Iron; Iron: analysis; lead; Lead: analysis; leaves; Manganese; Manganese: analysis; Plants; Plants: chemistry; seasonal dynamics; Soil; Soil: analysis; Trace Elements; Trace Elements: analysis; urban area pollution

Trace metal biomonitoring in the soil and the leaves of Quercus ilex in the urban area of Naples. - Alfani, a; Bartoli, G; Rutigliano, F a; Maisto, G; De Santo, a V (Biological trace element research, 1996)
The concentrations of Pb, Cu, Fe, and Mn were analyzed in surface deposit and tissue of Quercus ilex leaves from several sites of the urban area of Naples, exposed to different degrees of air pollution. These included some major roads with heavy traffic loads, squares, and three urban parks. The soil from the trunk base area of Q. ilex trees in the same sites was also analyzed for total and available metal contents. Pb, Cu, and Fe contents in the surface deposit and leaf tissue were significantly higher (p < 0.01) in leaves from roadside sites than in leaves from parks; significant correlations were found between deposit- and tissue-contents of Pb, Cu, and Fe. Mn content in leaves from roadside sites and in leaves from parks were similar and Mn content in the leaf deposit was irrelevant. Significant differences (p < 0.001) in both total and available Pb and Cu soil content were found between sampling sites. Also for available Fe and Mn soil content differences among sites were relevant, although the highest values were measured in soil from urban parks. A positive correlation between leaf and soil metal content was found only for Pb, thus suggesting that trace metal contents of leaves directly depend on atmospheric depositions. Seasonal variations of Pb, Cu, and Fe were pronounced at a polluted site, whereas no relevant seasonal variation was observed at a control site; moreover, metal accumulation was high at the polluted site. Mn content and seasonal dynamics were comparable at control and polluted sites.
Keywords: Air Pollutants; Air Pollutants: analysis; biomonitoring; copper; Copper: analysis; Environmental Monitoring; Holly Oak; Iron; Iron: analysis; lead; Lead: analysis; leaves; Manganese; Manganese: analysis; Plants; Plants: chemistry; seasonal dynamics; Soil; Soil: analysis; Trace Elements; Trace Elements: analysis; urban area pollution